2022
DOI: 10.3389/fbioe.2022.892385
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Stability of a Hemipelvic Prosthesis Based on Bone Mineral Density Screw Channel and Prosthesis Optimization Design

Abstract: In pelvic reconstruction surgery, the hemipelvic prosthesis can cause significant changes in stress distribution due to its high stiffness, and its solid structure is not suitable for osseointegration. The purpose of this study was to identify a novel bone mineral density screw channel and design the structure of the prosthesis so as to improve the distribution of stress, promote bone growth, and enhance the biomechanical properties of the prosthesis. The mechanical characteristics of bone mineral density scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
1
9
3
Order By: Relevance
“…A maximal stress of 101.6 MPa was observed when standing in the bipedal posture. With regard to stress of the pelvic ring, a peak stress of 44.1 MPa was observed on the upper endplate of the S1 vertebra, which is consistent with intuition and previous research in distribution and scales ( Iqbal et al, 2017 ; Liu et al, 2019 ; Zhou et al, 2022 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…A maximal stress of 101.6 MPa was observed when standing in the bipedal posture. With regard to stress of the pelvic ring, a peak stress of 44.1 MPa was observed on the upper endplate of the S1 vertebra, which is consistent with intuition and previous research in distribution and scales ( Iqbal et al, 2017 ; Liu et al, 2019 ; Zhou et al, 2022 ).…”
Section: Resultssupporting
confidence: 91%
“…The articular surface area limits the sacroiliac joint being inserted with up to three or four screws. Novel bone mineral density channels have been identified for screw insertion to improve the distribution of stress, promote bone growth, and enhance the biomechanical properties of the prosthesis ( Zhou et al, 2022 ). In our study, the orientation of the screws was more empirical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, cortical bone exhibits a Young’s modulus typically below 30 GPa, while the modulus of cancellous bone falls below 2 GPa ( Immel et al, 2021 ; Kang et al, 2021 ; Wu et al, 2021 ). The marked dissimilarity in mechanical attributes between the pelvis and the prostheses can instigate stress shielding, leading to complications such as periprosthetic bone resorption, aseptic loosening of prostheses, and periprosthetic fractures ( Kitamura et al, 2005 ; Arabnejad et al, 2017 ; Wu et al, 2021 ; Zhou et al, 2022 ). Earlier investigations of this topic have demonstrated that adaptations in geometric shapes, materials, or the integration of porous frameworks can mitigate prosthetic rigidity, thus tempering stress shielding ( Glassman et al, 2006 ; Iqbal et al, 2019 ; Vance et al, 2019 ; Zhou et al, 2022 ; Rana et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The marked dissimilarity in mechanical attributes between the pelvis and the prostheses can instigate stress shielding, leading to complications such as periprosthetic bone resorption, aseptic loosening of prostheses, and periprosthetic fractures ( Kitamura et al, 2005 ; Arabnejad et al, 2017 ; Wu et al, 2021 ; Zhou et al, 2022 ). Earlier investigations of this topic have demonstrated that adaptations in geometric shapes, materials, or the integration of porous frameworks can mitigate prosthetic rigidity, thus tempering stress shielding ( Glassman et al, 2006 ; Iqbal et al, 2019 ; Vance et al, 2019 ; Zhou et al, 2022 ; Rana et al, 2023 ). Among these strategies, the incorporation of porous architectures not only bestows a diminished elastic modulus but also fosters biological activity, enhancing the amalgamation of prostheses with host bone and promoting soft tissue adherence ( Chen et al, 2018 ; Lv et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%